ISOLATION, SCREENING, AND ANTIBACTERIAL ACTIVITY OF ENDOPHYTIC FUNGI ASSOCIATED WITH Acanthus ilicifolius L. IN INHIBITING THE GROWTH OF Methicillin-Resistant Staphylococcus aureus (MRSA) - Wiradana, Putu Angga; Anak Agung Ayu Putri Permatasari; I Gede Widhiantara; I Made Wisnu Adhi Putra; Ni Kadek Yunita Sari; Novaria Sari Dewi Panjaitan; Sri Puji Astuti Wahyuningsih; Mochammad Aqilah Herdiansyah (BRIN - Badan Riset dan Inovasi Nasional, 2025)
This study examines the phytochemical composition and antibacterial activity of endophytic fungi linked to the mangrove plant A. ilicifolius against methicillin-resistant Staphylococcus aureus (MRSA) in order to determine their bioprospecting potential. The surface-sterilized root, stem, and leaf tissues of A. ilicifolius yielded endophytic fungi. The workflow consisted of screening for viable isolates, culture under controlled circumstances, and molecular identification of the Internal Transcribed Spacer (ITS) section of fungal rDNA. Antibacterial activity was determined using agar well diffusion tests after extraction with methanol, ethyl acetate, and n-hexane solvent fractions. A total of 31 endophytic fungal isolates were recovered: 9 from roots, 15 from stems, and 7 from leaves. Among these, 5 isolates from roots (16.1%), 8 from stems (25.8%), and 5 from leaves (16.1%) exhibited inhibitory effects against MRSA. Isolate AK5, derived from root tissue, demonstrated the highest antibacterial activity and was molecularly identified as Chaetomium globosum strain NW 24 (Accession No. MN326469.1). The isolate revealed optimal growth at pH 5–6, with the maximum wet mycelial biomass (29.73 g) achieved on day 24 under shaker incubation. The methanol and ethyl acetate fractions had a considerably greater anti-MRSA efficacy than the n-hexane fraction. Phytochemical analysis of the methanolic extract indicated the presence of several bioactive components, including phenolics, tannins, flavonoids, saponins, alkaloids, and terpenoids, indicating that these constituents contribute to the reported antibacterial effects. Overall, our findings highlight the potential of A. ilicifolius-derived endophytic fungi as alternate sources of bioactive compounds for treating antibiotic-resistant infections, specifically MRSA.